Pengaruh Perencanaan Anggaran dan Pelaksanaan Anggaran terhadap Penyerapan Anggaran dengan Komitmen Organisasi sebagai Variabel Moderasi pada Badan Penelitian dan Pengembangan Kesehatan Republik Indonesia - Ferdinan Ferdinan; Isnurhadi Isnurhadi; Marlina Widiyanti; Mohamad Adam (JEMBATAN, 2020)
The implementation of a performance budget that carries the spirit of state financial reform is not as expected. One of the indications is that budget absorption is not optimal and concentrated at the end of the fiscal year. This will result in delays in benefits to be received and enjoyed by the community. This study was conducted to examine the effect of budget planning and budget implementation on budget absorption with organizational commitment as a moderating variable in the Health Research and Development Agency. The data collection techniques used in this study are the Likert scale. Workable samples totalling 59 respondents consisted of KPA, PPK, PPSPM and the Treasurer of Expenditure within the work unit of the Health Research and Development Agency involved in budget implementation using the census method. The data were data processed using multiple linear regression analysis and residual test. The results of this study indicate that budget planning has a significant positive effect on budget absorption while budget execution does not affect budget absorption. Organizational commitment does not strengthen or weaken the relationship between budget planning and budget execution towards budget absorption at the Health Research and Development Agency.